Intervensi Komunikasi Kesehatan Dalam Pencegahan Stunting - Nurdin, Ali; Labib, Mufti (State Islamic University of Sunan Ampel, 2025)
Stunting had emerged as a national issue and became a structured program implemented by both central and local governments. The dissemination of this program required effective communication in stunting prevention. This study aimed to describe and identify communication intervention strategies through the role of government, community participation, and communication strategies employed in the prevention of stunting in Karanggeneng Subdistrict, Lamongan Regency.This research employed a descriptive-qualitative design with a Community-Based Communication Strategies (CBSC) approach, which referred to the role of government, community participation, and communication strategies applied in stunting prevention. Data were collected through interviews, observations, and documentation. Interviews were conducted with 10 health team informants and 5 supporting community informants. The data were analyzed using the flow model of Miles & Huberman and were supported by NVivo 12 software. The findings revealed that communication interventions in stunting prevention were carried out by involving the role of government, community participation, and the use of health communication strategies as part of the CBSC approach. The government’s role was realized through stunting prevention programs involving doctors, medical staff, nurses, and village midwives. Community participation was manifested through the support of activities organized by PKK, health cadres, Fatayat NU, A’isyiyah, and even religious and community leaders by creating innovations based on health services. Health communication strategies were conducted collaboratively among stakeholders by employing interpersonal face-to-face communication, routine meetings, social media, health campaigns, health program innovations, and healthy menu creation competitions. The model of health communication intervention in stunting prevention could serve as a role model for stunting prevention in other regions with similar community characteristics.